A Watch of Nightingales - Wieland, Liza (Book collections on Project MUSE., 2009)
A modest, quiet woman, Mara Raynor never dreamed she'd one day find herself in charge of the small private school in Washington, D.C., where for many years she taught music and choir. But after the unexpected death of her husband, the school's headmaster, Mara finds herself thrust into the public eye, burdened not just with the responsibilities of acting headmaster--a role she never wanted--but also with a potentially explosive political and religious controversy that tests parents' and school administrators' spirit of tolerance. When a Sikh student is caught wearing a ceremonial knife on school grounds, fear spreads among parents and the school board. Coming at the same moment as the disappearance of Mara's teenage daughter, the controversy quickly assumes a far more personal nature. Not just any student, the Sikh boy is both the son of a woman with whom Mara shares a complicated past and--as Mara soon discovers--her own daughter's boyfriend. As it moves ...